Pengaruh Bauran Promosi Konvensional terhadap Peningkatan Pasien Baru di Klinik Gigi Dent Smile Cabang Jakarta Utara dan Jakarta Pusat - Emanuela, Febrina; Rohendi, Acep; Sukajie, Bambang (Jurnal EMT KITA, 2026)
This study examines the influence of conventional promotion strategies on the acquisition of new patients at Dent Smile Dental Clinic in North and Central Jakarta. The research aims to identify which forms of conventional promotion are effective in increasing patient visits. Using a quantitative approach with survey data from 1200 respondents, the study applied simple linear regression analysis supported by ANOVA to test the impact of four promotional variables: brochure distribution, word of mouth (WOM), banner signage, and direct community outreach programs (in schools and offices). The findings indicate that brochure distribution has a positive and significant effect on attracting new patients, confirming the continued relevance of printed media for segments with limited digital literacy. In contrast, WOM and banner signage show significant but negative effects, suggesting that poor service experiences or ineffective visual design may weaken patient acquisition. Meanwhile, direct community outreach programs show no significant effect, functioning more as brand awareness and health education rather than a direct driver of patient growth. This research highlights the importance of selective implementation of conventional promotion and its integration with digital strategies. The study contributes managerial insights for clinic marketing practices and academic evidence on the role of traditional media in modern healthcare promotion.
Keywords: Conventional Promotion; Brochure; Word Of Mouth; Banner Signage; Healthcare Marketing